2017
DOI: 10.1063/1.4986339
|View full text |Cite
|
Sign up to set email alerts
|

Boosting surface charge-transfer doping efficiency and robustness of diamond with WO3 and ReO3

Abstract: An advanced charge-transfer yield is demonstrated by employing single monolayers of transition-metal oxides—tungsten trioxide (WO3) and rhenium trioxide (ReO3)—deposited on the hydrogenated diamond surface, resulting in improved p-type sheet conductivity and thermal stability. Surface conductivities, as determined by Hall effect measurements as a function of temperature for WO3, yield a record sheet hole carrier concentration value of up to 2.52 × 1014 cm−2 at room temperature for only a few monolayers of cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…[32][33][34][35][36] Along with the extreme semiconducting properties such as ultrawide bandgap of 5.5 eV, high thermal conductivity, and high breakdown field, diamond electronic devices provide the attractive route to develop the next-generation electronic devices able to operate under high-power, high-frequency, and high-temperature conditions. The surface density of the 2DHG on H-terminated diamond is as high as 10 13 cm −2 and can reach 10 14 cm −2 when properly selecting the surface molecular or oxides.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34][35][36] Along with the extreme semiconducting properties such as ultrawide bandgap of 5.5 eV, high thermal conductivity, and high breakdown field, diamond electronic devices provide the attractive route to develop the next-generation electronic devices able to operate under high-power, high-frequency, and high-temperature conditions. The surface density of the 2DHG on H-terminated diamond is as high as 10 13 cm −2 and can reach 10 14 cm −2 when properly selecting the surface molecular or oxides.…”
Section: Resultsmentioning
confidence: 99%
“…64 Lastly, recent work showed that WO 3 is able to tune the surface charge transfer of diamond. 67 In fact, the transfer doping efficiency with WO 3 was the highest per minimal surface acceptor coverage reported to date, marking a sizable advance in 2D diamond-based electronic devices. This recent work on WO 3 , in combination with that of the past, attests to the wide variety of applications this material continues to have.…”
Section: Inorganicsmentioning
confidence: 98%
“…], Nb2O5 [9] and ReO3 [10]. Though encouraging progress has recently been reported for FET devices that incorporate some of these EAO materials [11][12][13], the challenges associated with their integration into a diamond FET architecture and associated process flow have thus far limited their full potential to enhance both device performance and stability of operation.…”
Section: Introductionmentioning
confidence: 99%